General description of crimes against public order (Journal of actual problems of jurisprudence, 2018)
This work addresses the problem of the definition of crimes against the public order. The author devotesgreat attention to public order as the object of crimes and the rules of crimes leads the group.Pays particular attention to the composition of hooliganism as the most dangerous crimes from this groupare often theoretical provisions aimed at combating these forms of crime. The author cites the qualificationrules of hooliganism and vandalism, along with this proposed concrete ways and means to prevent crimesof this group.Keywords:public peace, public safety, criminal legal norms, criminal venture, hooliganism.